Hypoxaemia without Respiratory Distress in a Patient with Oral Cancer: A Case Report - Mansi Dey; Akash Gupta; Bibhu Prasad Mishra; Malini Kulshrestha; Arjun Agarwal (Journal of Clinical and Diagnostic Research)
Methaemoglobinaemia is a rare disorder caused by oxidisation of divalent ferrous-iron (Fe2+) of Haemoglobin (Hb) to ferric-iron (Fe3+) of Methaemoglobin (MetHb), and it has a life-threatening potential. Here, we present a case of oral cancer with methaemoglobinaemia. A 40-year-old male patient reported to us with a swelling on the left-side of the face since six months. He was diagnosed with resectable oral cancer and hence planned for surgery. He had a very peculiar finding with low SpO2 without any respiratory distress. After obtaining pre-anaesthetic-clearance, he was operated under general anaesthesia. Brown ring test was positive, which was suggestive of methaemoglobinaemia. Serum methyloglobin was found to be present in a concentration of 9.7% when the blood sample was sent for testing. Patient was administered 5 mL of Methylene Blue (MB) intravenously in 100 mL Normal Saline (NS) at 3-4 drops per minute within 1/2-1 hour daily. Improvement in SpO2 on the pulse-oximeter was observed, from about 20% to about 66% in five days after administration of MB. Thus, it was concluded that methaemoglobinaemia is not always a life threatening condition, and knowledge about previous history of exposure to the substance that might lead to methaemoglobinaemia is important, so that such substances can be avoided in the future to prevent further worsening of the condition.